Kebijakan Kerukunan Antarumat Beragama dan Peningkatan Modal Sosial di Kota Padang - Tanjung, Khairumen (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This article describes the diversity in Padang City society which can be a potential for building strength and harmony in social life. One aspect of diversity is differences in religion and beliefs between religious communities. This study aims to understand inter-religious harmony and increase social capital in Padang City. This article was studied using qualitative methods, where data was collected through in-depth interviews as well as observation and documentation. Then the data is analyzed using an interactive model, which includes: data reduction steps, data presentation, and data verification, which is supported by triangulation. The results of this study found that inter-religious harmony and social capital in Padang City are quite good. Obstacles in religious harmony include a lack of funding support for activities, a lack of understanding of the important meaning of religious harmony, and there are still conflicting perceptions between interfaith figures in understanding religious harmony. Thus, this policy study recommends the need to increase religious harmony through: (1) further education and outreach programs to the community; (2) intensive dialogue between religious figures and between interfaith youth; and (3) additional support from the Ministry of Religion and all related elements of society. The results of this study can provide information to stakeholders and input for making better policies.